From Isolation to Momentum: Understanding Natuna’s Village Development Through Circular Causation - Yogi Pasca Pratama; Dinarjati Eka Puspitasari; Hurng-Jyuhn Wang; Anang Pra Yogi; Salju Indara Zeith Geisth; Hastin Nariswari (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
Strategic borderlands and regional development In strategic border regions,?we find a complex politico-geographical dynamic between the imperatives of state territorial security on one hand, and economic under-development on the other. It’s about Natuna?Regency, Indonesia's